Letter - Spragg, Charles G.
034-0029-001 BIRMINGHAM TRADES COUNCIL Established 1866 Telephone : CENtral 3435 Secretary: Councilor C.G. SPRAGG. J P. UNITY CHAMBERS 262 CORPORATION STREET BIRMINGHAM 4 EC/CGS 27th. April 1942. The Joint Secretaries, National Council of Labour Transport House, SMITH SQUARE LONDON S.W.1. Dear Colleagues, I am directed by my Executive Committee to forward to you a copy of the following Resolution which was unanimously carried at the last meeting:- Resolved: "That this Council urges the National Council of Labour to approach the American Government to intervene in Vichy on the following points:- 1. To endeavour to stop the extradition of former members of the International Brigade to Germany and German occupied Countries and Italy. 2. To grant French exit permits to former International Brigaders. 3. To permit the distribution of relief to International Brigades in French and Spanish Internment Camps by accredited relief organisations in France, Spain, Portugal and Switzerland." I am directed to express the hope that your Council will do its utmost to obtain the help of the American Government on this matter in view of the plight of these veterans in the fight for democracy. Yours sincerely, Charles G. Spragg Secretary. 292/946/34/29